Computational impact responses of reinforced concrete slabs - Shahrul Niza, Mokhatar; Redzuan, Abdullah; Ahmad Kueh, Beng Hong (Techno-Press, 2013)
The responses of reinforced concrete slabs subject to an impact loading near the ultimate load range are explored. The analysis is carried out on a simply supported rectangular reinforced concrete slab using a nonlinear explicit dynamic procedure and considering three material models: Drucker-Prager, modified Drucker-Prager, and concrete damaged plasticity, available in the commercial finite element software, ABAQUS/Explicit. For comparison purposes, the impact forcetime response, steel reinforcement failure, and concrete perforation pattern are verified against the existing experimental results. Also, the effectiveness of mesh density and damage wave propagation are studied independently. It is shown that the presently adopted finite element procedure is able to simulate and predict fairly accurate the behavior of reinforced concrete slab under impact load. More detailed investigations are however demanded for the justification of effects coming from an imperfect projectile orientation as well as the load and structural surface conditions, including the impulsive contacted state, which are inevitable in an actual impact environment.